Prosthetic rehabilitation of untailored defects using patient-specific implants - Sudheer Kondaka; Vankudoth Dal Singh; Chakradhar Vadlamudi; Lakshmana Rao Bathala (Wolters Kluwer Medknow Publications, 2022)
The restoration of speech, deglutition, mastication, and respiration in patients with bimaxillary resection involving the maxillae, hard and soft palates, and paranasal sinuses poses a significant challenge. This clinical report describes the prosthodontic management of a patient with bilateral maxillectomy caused due to post-COVID-19 mucormycosis. A patient-specific implants (PSI) that matched the remnants of the zygoma complex was designed to improve the patient's severely impaired speech and swallowing. The patient's postsurgical anatomy was first visualized using three-dimensional computed tomography data. Following that, a customized zygoma-supported titanium framework was designed to support the prosthesis based on the data. Two weeks after the framework was installed, an open-tray impression was made and the prosthesis was fabricated. These findings suggest that PSI-retained prosthesis can be considered in cases with severely compromised maxillary bone anatomy, impaired oral functioning, and no viable conventional reconstruction options.